المقاومة السياسية الليبية خلال الحربين العالميتين 1916 ــــــ 1945 - رحاي, محمد (جامعة الوادي - University of Eloued, 2021)
الملخص: يهدف هذا المقال إلى تسليط الضوء على مرحلة هامة من تاريخ ليبيا المعاصرة ما بين 1916 و 1945،و التي تجمع بين الاحتلال الايطالي لليبيا قبل الحرب العالمية الثانية، و الاحتلال البريطاني الفرنسي لها بعد الحرب، وتقسيم البلاد بينهما ،وقد تناول المقال النشاط السياسي لليبيين من أجل الوحدة داخل ليبيا ، و في المهجر في كل من مصر وسورية و تونس، و ذلك عند قمع الايطاليين للمقاومة المسلحة و كذا تحالف السنوسيين مع بريطانيا ومشاركة الجيش الليبي في الحرب العالمية الثانية إلى جانب الحلفاء، ونتائج الحرب على ليبيا التي أدىت إلى تقسيمها بين بريطانيا و فرنسا . This study aims to focus on of the libyan contemporary history stages(1916 -1945).when libya was under both occupations the Italien before world war two and the British and the French occupation after it, where they wanted to to devide the country between them.The paper deals with the political activities inonder to get union whether inside libya or abroad( in Egypt, Syria and Tunis) during the italian suppression to the libyan leader Umar Al-mokhtar resistance. Then the alliance between the Sanussis and the British. In addition to the participation of the libyan arme alondside to the allies forces during world war two. Finally, the main result of this war was devision of libya between the British and the French.
مقال
Keywords: ليبيا؛ بريطانيا؛ فرنسا؛ الحرب العالمية؛ المقاومة السياسية; libya, The British, The French, world war, The Allies